Therapeutisches Management eines „kissing nevus“ des Augenlids - Gaca, P J; Rejdak, R; Toro, M D; Lewandowicz, M; Kopecky, A; Somfai, G M; Nowak, R; Heindl, L M (Die Ophthalmologie, 2024)
Congenital divided melanocytic nevi of the upper and lower eyelid are rare pigmented changes of the eyelids. These processes are also known as "kissing nevi," "panda nevi," and "split ocular nevi," and were first described by Fuchs in 1919. About 120 cases have been described in the literature so far. Congenital melanocytic nevi are either present at birth (small nevi are already found in about 1% of neonates) or manifest predominantly during the first decade of life. These rare melanocytic changes of the eyelids should be controlled regularly, as malignant transformation can occur. The actual incidence of malignant transformation is highly variable in the literature, ranging from 2 to 40% depending on the duration of follow-up, with an average of 14% for the whole lifetime. Moreover, nevi of the eyelids may be considered cosmetically disturbing and cause functional problems. Therapeutic removal (dermabrasion, cryotherapy, laser therapy, and surgical excision with ophthalmoplastic reconstruction) is rarely medically indicated due to the low risk of malignant transformation. Removal can be performed in cases of secondary amblyopia in ptosis, compression of the lacrimal point, epiphora, or cosmetic desire. Treatment becomes necessary not only in case of suspicious manifestation or impairment of eyelid function, but it also helps to avoid possible bullying at school among children and is recommended at age 4 to 6 (before school age).
Keywords: Eyelids; Nevus, Epithelioid and Spindle Cell; předškolní dítě; Humans; Cell Transformation, Neoplastic; Nonsurgical management; nádorová transformace buněk; epiteloidní a vřetenobuněčný névus; laserová terapie; Surgical management; Laser Therapy; Child, Preschool; nádory kůže; Infant, Newborn; Regenerative medicine; Nevus, Pigmented; novorozenec; pigmentový névus; oční víčka; lidé; Malignant transformation; dítě; Child; Skin Neoplasms; Congenital divided melanocytic nevi